The Development of International Law in the Age of Globalization: Challenges and Opportunities - Permai Yudi; Berlian Berlian (Ridwan Institute, 2023)
This journal article aims to analyze the development of international law in the era of globalization, with emphasis on the challenges and opportunities it faces. In this context, it is necessary to consider various aspects, including global power dynamics, the role of international organizations, and the role of states in safeguarding their national interests. This research uses qualitative methods with a literature review approach. Literature review is a systematic, explicit and reproducible method for identifying, evaluating and synthesizing research works and thoughts that have been produced by researchers and practitioners. The results of this study conclude that in this increasingly connected and complex context, international law plays an important role in regulating relations between states and resolving disputes at the global level. However, global power dynamics, the role of international organizations, and global environmental protection are the main challenges that must be faced in the development of international law.